Force decline after low and high intensity contractions in persons with multiple sclerosis. Issue 3 (March 2019) - Severijns, Deborah; Cuypers, Koen; Meesen, Raf; Feys, Peter; Zijdewind, Inge
Highlights: Mechanisms underlying force decline differed between controls and persons with MS. Force decline during strong contractions is dominated by changes in peripheral (muscle) properties. Force decline during weak contractions is associated with sense of fatigue in persons with MS. Abstract: Objective: Force decline during strong contractions is dominated by changes in the periphery whereas during weaker contraction changes in voluntary activation become more important. We compared force decline and contributing factors in persons with multiple sclerosis (PwMS) during low and high intensity contractions. Methods: Index finger abduction force, force evoked by electrical stimulation of the ulnar nerve at rest (RTw), and during MVCs were investigated in 19 PwMS and 19 controls. Participants performed contractions in sets of six contractions (7 s-on, 3 s-off) at 25% or 80% MVC. After each set, a 5 s-MVC was performed with superimposed nerve stimulation followed by RTw. Contractions were repeated until MVC dropped below 80% of initial MVC. Results: Low compared to high intensity contractions caused a greater decline in voluntary activation and a smaller decline in RTw. Compared to controls, PwMS accomplished equal sets of contractions but showed a smaller decline in RTw. Female PwMS showed poorer voluntary activation. The number of low intensity contractions was associated with sense of fatigue in PwMS. Conclusion: Although, no difference in fatigability was observed, the mechanism contributing to force decline differed between PwMS and controls during submaximal contractions. Significance: During weak contractions, fatigue and fatigability are associated in PwMS.